Analisis Pelatihan Dan Pengembangan Karir Terhadap Kinerja Karyawan Di Divisi Regional I Sumatera Utara Pt Kereta Api Indonesia - Alvin Junior Simatupang; Syafril Gustiawan; Galih Ramadhan; Daud Arifin (JURNAL MANAJEMEN & ORGANISASI REVIEW (MANOR), 2026)
This template of MANOR: This study aims to analyze the effect of training and career development on employee performance at PT Kereta Api Indonesia (Persero) Regional Division I North Sumatra, with motivation as a moderating variable using the Moderated Regression Analysis (MRA) approach. The study employed a descriptive qualitative approach to gain an in-depth understanding of the implementation of training and career development and their implications for employee performance. Data were collected through in-depth interviews, observations, and documentation involving employees and management personnel responsible for human resource management. The results indicate that training has a positive impact on improving employees’ technical and non-technical competencies, including operational skills, discipline, communication, and work professionalism. Career development also influences employee motivation and performance improvement, although several obstacles related to promotion opportunities, job mobility, and transparency in career development were still identified. Furthermore, work motivation was found to strengthen the relationship between training and career development on employee performance. Therefore, the integration of training, career development, and work motivation becomes an important factor in improving employee performance effectiveness sustainably. This study is expected to contribute theoretically to the development of human resource management science and serve as a consideration for companies in formulating more effective employee development strategies